Household Characteristics, Cost of Illness and Coping Mechanism of Families of Hospitalized Acute Encephalitis Syndrome Children: A Mix Method Study - Gitali Kakoti; Bishnu Das Ram; Mandira Chetri (Medsci Publications, 2023)
Background: AES is responsible for causing high social and economic burden to the affected families. The study was conducted to know the household characteristics, cost of illness and coping strategy adopted by the family members of AES children admitted to a tertiary care facility in Assam, India. Methods: It was a sequential exploratory mixed method study, with a cross-sectional survey among AES children and their guardians, followed by In Depth interview. Results: Out of 51 cases 55% were male. The median age was 11 years. 53% of the families belonged to lower socioeconomic class. 96% of families reported to reside in rural areas. Commonly reported household assets were mobile phone 94%, bicycle 86%, television 31% and motorcycle 29%. Three major themes were emerged to contribute towards economic burden. The first major theme is "Direct cost" due to patient transportation cost (mean Rs 1161.00) and hospital costs: mostly due to medicinal cost (mean Rs1955.00), investigational cost (mean Rs 2920.00) and food cost (mean Rs 8375.00). The second theme "Indirect cost" is due to work days loss: 100% care providers had missed work days during hospital stay of their children and 84% had missed work days during post hospital care. The third theme is "Inherent cost spotted through coping mechanisms" which mostly 94% included borrowing money from the market and 31.4% selling household assets. Conclusion: Cost of illness is a huge burden to the AES afflicted families which demands reforms in health care financing and reimbursement in current context.